2014
DOI: 10.1139/cjfr-2014-0199
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest needle abscission resistance of balsam fir (Abies balsamea) is modified by harvest date

Abstract: Earlier harvest dates have become necessary for Canadian Christmas tree producers to meet international demand, though by harvesting these trees early they may experience poor needle retention. The objective of this study is to understand the effect of harvest date on needle retention and link those changes to cold acclimation. In one experiment, balsam fir trees with varied needle abscission resistance (NAR) were collected in October and in January and monitored for needle retention. This was repeated for 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…There are significant differences between in needle retention duration (NRD) between balsam fir genotypes. Low NRD genotypes would abscise needles in less than 20 days while high NRD genotypes would not abscise needles until after 40 days [20]. It was found high needle retaining genotypes changed very little from September to January in needle retention, whereas low needle retaining genotypes had increased needle retenton [20].…”
Section: Physiological Changes Occurring During Abscission In Balsam mentioning
confidence: 90%
See 2 more Smart Citations
“…There are significant differences between in needle retention duration (NRD) between balsam fir genotypes. Low NRD genotypes would abscise needles in less than 20 days while high NRD genotypes would not abscise needles until after 40 days [20]. It was found high needle retaining genotypes changed very little from September to January in needle retention, whereas low needle retaining genotypes had increased needle retenton [20].…”
Section: Physiological Changes Occurring During Abscission In Balsam mentioning
confidence: 90%
“…Abscission, in general, is regulated by environmental as well as developmental cues. For example, cold acclimation increases abscisic acid (ABA) and certain sugars in conifers, which tends to delay postharvest needle abscission [20]. It has been shown that cold acclimation is triggered through environmental signals of both decreasing temperature and photoperiod [21].…”
Section: Abscission In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…After harvest and display in water, typically no abscission occurs for between one and 2 weeks. Needle abscission commencement is usually noted by a loss of 1% dry needle weight and gradually accelerates until 100% needle loss, which has been referred to as needle retention duration or, more recently, needle abscission resistance (NAR; MacDonald et al, 2014a , b ). The length of time between needle abscission commencement and completion has varied between 1 week ( MacDonald et al, 2011b ) and 4 weeks ( MacDonald et al, 2014b ), though 2 weeks is a reasonable estimate in most cases.…”
Section: Dynamics Of Needle Abscission In Balsam Firmentioning
confidence: 99%
“…Regardless, early harvest practices combined with warmer autumn temperatures contribute to accelerated postharvest abscission. It’s been noted repeatedly that trees harvested in September or October tend to have lower needle retention than trees harvested in November or December ( Mitcham-Butler et al, 1987 ; Chastagner and Riley, 2007 ; MacDonald et al, 2014b ). MacDonald and Lada (2008) estimated that 1 in 3 trees shed all needles in less than 3 weeks in normal shipping/storage conditions.…”
Section: Introductionmentioning
confidence: 99%